Attitudes in the Flemish Political Climate Debate: A Linguistic Analysis - Van Praet, Wout (Politics of the Low Countries, 2025)
This study investigates the climate communication by the main political parties in Flanders. Its aim is to describe explicit and implicit evaluations that parties make about climate change and climate-related policies in the communication on their websites. To analyse parties’ opinions on climate action, the study uses the system of Appraisal (Martin & White, 2005), which provides a framework for interpreting expressions of attitude as a social tool to engage with others. The results show that the climate communication by Flemish political parties strikes an overall positive note. Differences in emphases aside (e.g., on quality of life vs. financial profitability), there seems to be a consensus on the need for, and value of, climate action. The communication by Vlaams Belang stood out as an exception: its negative tone, and critical content, gives signs of climate scepticism, forming a counterposition in the political climate change debate.